Study of development of kazakhstani-indian relations in the spheres of culture, education, and science - Taubaldiyeva, D S (Journal of Oriental Studies, 2016)
The article is dedicated to study of development of Kazakhstani-Indian relations in the spheres of culture, education, and science. The article contains materials that have been found in the Central State Archive of RoK.